HUBUNGAN ANTARA BENTUK KASKO MODEL KAPAL IKAN DENGAN TAHANAN GERAK - Yopi Novita; Budhi H. Iskandar (Buletin PSP, 2008)
This paper describe results of the experiment of resistance from four different types of fishing boat hull in Indonesia such as U-bottom, round bottom, round flat bottom and akatsuki. The objectives of the research are to estimate the value of the resistance from different type of fishing boat hull, and (2) to estimate the type of hull which is the highest and lowest resistance.The research was carried out in the flume tank by using the model of fishing boat hull with scale 1 : 40.The four different types of hull were investigate in the water flow. The data of resistance were taken when the fishing boat in stable condition, heaving, pitching and moving to the right and left. The 10 data were taken from each different types of hull.The results of the experiment shows that the akatsuki type is the highest resistance, followed by U-bottom, round flat bottom and round bottom. The percentage of resistance from each type of hull shows that the akatsuki 0,19% higher than U-bottom. While the resistance of U-bottom 8,05% higher than round flat bottom, and the resistance round flat bottom 3,23% higher than round bottom.